Money and finance in world economic order - Panchamukhi, V. R. (Vadiraj Raghawendracharya), 1936-; Raipuria, Kalyan M.; Tandon, Rameshwar; Research and Information System for the Non-aligned and Other Developing Countries (New Delhi : Indus Pub. Co., 1987)
Contributed papers on developing countries.
"Issued under the auspices of Research and Information System for the Non-aligned and Other Developing Countries."
Includes bibliographical references and index.
Keywords: Money -- Developing countries; Finance -- Developing countries